The Analysis of the Evaporation Effect on Moisture Soil under Intermittent Operation of Ground-source Heat Pump. (February 2019) - Shang, Yan; Dong, Ming; Mu, Lin; Liu, Xiaohua; Huang, Xiaowan; Li, Sufen
Abstract: Based on the porous theory, a three-dimensional model is presented in this paper to study heat and mass transfer characteristics of moisture soil, which was considered as unsaturated porous media. Compared with saturated model and experiment results, the simulation is validated on the heating mode of the heat pump system. The distribution of the geo-temperature is predicted by using the model. Moreover, the evaporation especially surface evaporation is taken into account. The influencing factors such as soil saturated moisture content, soil actual moisture content and wind velocity are also studied in simulation. The results show that the evaporation has a great impact on the soil temperature field. Under the surface evaporation effect, the soil temperature decreases quickly in soil exothermic process and increases slowly in the recovery process. As the soil moisture rate and wind velocity increasing, the soil temperature falls quickly and recovers slowly under the intermittent operation of the heat pump system. The opposite results have been obtained with the effect of soil actual moisture content. Furthermore, all the results indicate that the effect attenuates with the depth of soil.